340 W average power output of diode-pumped composite ceramic YAG/Nd:YAG disk laser. (14th October 2016) - Jia, Kai; Jiang, Yong; Yang, Feng; Deng, Bo; Hou, Tianjin; Guo, Jiawei; Chen, Dezhang; Wang, Hongyuan; Yang, Chuang; Peng, Chun
Abstract: We report on a diode-pumped composite ceramic disk laser in this paper. The composite ceramic YAG/Nd:YAG disk consists of 4 mm thick pure YAG and 2 mm thick Nd:YAG with 1.0 at.% doping concentration. The slope efficiency of the composite ceramic disk laser is 36.6% corresponding to the maximum optical–optical efficiency of 29.2%. Furthermore, 340 W average power output was achieved at the absorbed pump power of 1290 W.